Teachers’ and students’ perspectives on using authentic materials in teaching English: A survey at Ha Nam Teachers’ Training College” - Phùng, Thị Huyền (H.: ĐHNN, 2017)
The findings of the survey reveal that most of the teachers and students indicated positive attitudes toward providing authentic materials in their classes. Through analyzing the responses in the students’questionaire and the semi-structured interviews with the teachers and students, it can be concluded that such positive attitudes were grounded on many advantages of authentic materials in improving and developing language skills. Besides, authentic materials have a positive effect on learners’ motivation, bridge the gap between classroom setting and the everyday life language in the real world and provide authentic cultural information. According to the obtained results, both teachers and students acknowledged the existence of a number of difficulties that they encountered in using authentic materials such as time, difficult language, unknown words, facilities, culture information and curriculum. The findings here are consistent with the mentioned literature of the advantages of using authentic materials. Generally, there is an agreement between the teachers and students in the perspectives on the pros and cons of using authentic materials. On the other hand, some disagreements are found in the participant responses. The first disagreement is found in their responses concerning the difficulty of so many unknown words in authentic materials. Another mismatch between the participants is observed in regard to the suitable level of students to work with authentic materials. The next difference between the teachers’and students’perspectives is on their favorite types of authentic materials.